Aplikasi Model MapDAS untuk Simulasi Karakteristik Hidrologi DAS Mikro yang Didominasi Perkebunan Sawit: Application of MAPDAS Model for Micro-Watersheds Hydrological Characteristics Simulation Dominated by Oil Palm Plantation - Faqihna Pidin; Suria Darma Tarigan; Budi Kartiwa (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Land use change in the plantation expansion can potentially cause soil degradation leading to drought in the dry season and flooding in the wet season. Hydrological model is important to simulate impact of land use change in the plantation on the discharge fluctuation. This study used MAPDAS Model for simulation purpose. MAPDAS Model uses 4 (four) main simulation input parameters, which are runoff coefficient (Kr), lag time, hydrographic network flow rate, and slope flow rate. The objective of the study are 1) to examine the accuracy of the model in 3 effective-rainfall determination method; 2) to study the hydrology characteristics of micro-watershed dominated by oil palm plantation using MAPDAS Model with 3 effective rainfall determination scenarios. The result showed that the use of MAPDAS Model with rainfall input based on Kr, infiltration index (F), and SCS-CN method gave value of runoff coefficient ranged from 12 to 70%. The MAPDAS Model is able to simulate hydrological characteristics with good result, shown by the CE value which is more than 0.7. catagorized as high to very high accuracy.